Lysosomal K+ channel TMEM175 promotes apoptosis and aggravates symptoms of Parkinson's disease. (1st August 2022) - Qu, Lili; Lin, Bingqian; Zeng, Wenping; Fan, Chunhong; Wu, Haotian; Ge, Yushu; Li, Qianqian; Li, Canjun; Wei, Yanan; Xin, Jing; Wang, Xingbing; Liu, Dan; et al.
Abstract: Lysosomes are degradative organelles and play vital roles in a variety of cellular processes. Ion channels on the lysosomal membrane are key regulators of lysosomal function. TMEM175 has been identified as a lysosomal potassium channel, but its modulation and physiological functions remain unclear. Here, we show that the apoptotic regulator Bcl‐2 binds to and inhibits TMEM175 activity. Accordingly, Bcl‐2 inhibitors activate the channel in a caspase‐independent way. Increased TMEM175 function inhibits mitophagy, disrupts mitochondrial homeostasis, and increases production of reactive oxygen species (ROS). ROS further activates TMEM175 and thus forms a positive feedback loop to augment apoptosis. In a 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP) mouse model of Parkinson's disease (PD), knockout (KO) of TMEM175 mitigated motor impairment and dopaminergic (DA) neuron loss, suggesting that TMEM175‐mediated apoptosis plays an important role in Parkinson's disease (PD). Overall, our study reveals that TMEM175 is an important regulatory site in the apoptotic signaling pathway and a potential therapeutic target for Parkinson's disease (PD). Synopsis: The anti‐apoptotic mitochondrial protein Bcl‐2 regulates lysosomal K + channel TMEM175. TMEM175 forms a positive feedback loop with ROS to augment apoptosis and promote the death of DA neurons in Parkinson's disease. Anti‐apoptotic mitochondrial protein Bcl‐2 binds to and regulates lysosomal potassium channel TMEM175. TMEM175 inhibits mitophagy, impairs mitochondrial function, and consequently increases ROS production. ROS activates TMEM175 through a positive feedback loop to augment apoptosis. TMEM175‐mediated apoptosis promotes the death of dopaminergic neurons in Parkinson's disease. Abstract : The anti‐apoptotic mitochondrial protein Bcl‐2 regulates lysosomal K + channel TMEM175. TMEM175 forms a positive feedback loop with ROS to augment apoptosis and promote the death of DA neurons in Parkinson's disease.